Balloon-borne observations of the development and vertical structure of the Antarctic ozone hole in 1986 - Hofmann, D. J.; Harder, J. W.; Rolf, S. R.; Rosen, J. M. (1987)
The vertical distribution of ozone measured at McMurdo Station, Antarctica using balloon-borne sensors on 33 occasions during November 6, 1986 - August 25, 1986 is described. These observations suggest a highly structured cavity confined to the 12-20 km altitude region. In the 17-19 km altitude range, the ozone volume mixing ratio declined from about 2 ppm at the end of August to about 0.5 ppm by mid-October. The average decay in this region can be described as exponential with a half life of about 25 days. While total ozone, as obtained from profile integration, declined only about 35 percent, the integrated ozone between 14 and 18 km declined more than 70 percent. Vertical ozone profiles in the vortex revealed unusual structure with major features from 1 to 5 km thick which had suffered ozone depletions as great as 90 percent.